2014
DOI: 10.1016/j.maturitas.2014.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Ospemifene, a non-oestrogen selective oestrogen receptor modulator for the treatment of vaginal dryness associated with postmenopausal vulvar and vaginal atrophy: A randomised, placebo-controlled, phase III trial

Abstract: Once-daily oral ospemifene 60 mg was effective for the treatment of VVA in postmenopausal women with vaginal dryness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(144 citation statements)
references
References 28 publications
11
130
0
3
Order By: Relevance
“…Evidence of efficacy of ospemifene is based on randomised controlled trials and long term safety data are available [30]. The approved indication in Europe is for 'treatment of moderate to severe symptomatic vulvar and vaginal atrophy (VVA) in post-menopausal women who are not candidates for local vaginal oestrogen therapy'.…”
Section: Genitourinary Syndrome Of Menopausementioning
confidence: 99%
“…Evidence of efficacy of ospemifene is based on randomised controlled trials and long term safety data are available [30]. The approved indication in Europe is for 'treatment of moderate to severe symptomatic vulvar and vaginal atrophy (VVA) in post-menopausal women who are not candidates for local vaginal oestrogen therapy'.…”
Section: Genitourinary Syndrome Of Menopausementioning
confidence: 99%
“…The effectiveness of 60 mg/day ospemifene was assessed by Portman et al [36] in a randomised, placebo-controlled, phase III trial on 314 women, who reported vaginal dryness as the most bothersome symptom of VVA. There were 33.8% responders in the treatment group compared to 7.1% of patients receiving a placebo.…”
Section: Selective Oestrogen Receptors Modulatorsmentioning
confidence: 99%
“…Ospemifene is a selective estrogen receptor modulator (SERM) [31]. Several studies have shown efficacy [32][33][34][35][36][37][38]. A pivotal 12 week randomized trial showed that ospemifene was shown to be effective and well tolerated for the treatment of the symptoms of vaginal dryness and dyspareunia associated with vulvovaginal atrophy over and above the use of provided lubricants [32].Subsequent studies have confirmed efficacy and safety over 12 months.…”
Section: Ospemifenementioning
confidence: 99%
“…A pivotal 12 week randomized trial showed that ospemifene was shown to be effective and well tolerated for the treatment of the symptoms of vaginal dryness and dyspareunia associated with vulvovaginal atrophy over and above the use of provided lubricants [32].Subsequent studies have confirmed efficacy and safety over 12 months. Hot flushes are the most common reported treatment related adverse events in about 7% of patients [34,37]. Endometrial safety was evaluated in six randomized, double-blind, placebo controlled, parallel-group studies lasting up to 52 weeks [33].…”
Section: Ospemifenementioning
confidence: 99%